1979
DOI: 10.1136/vr.104.11.235
|View full text |Cite
|
Sign up to set email alerts
|

The biological selenium status of livestock in Britain as indicated by sheep erythrocyte glutathione peroxidase activity

Abstract: The reliability of erythrocyte glutathione peroxidase activity as an indicator of selenium status in livestock is discussed. Based on this measurement, a survey is described of the biological selenium status of sheep on each of 329 farms in Britain. Results showed that 47 per cent of these farms were probably unable to provide grazing livestock with sufficient selenium to maintain blood levels greater than 0.075 microgram per ml. Increased selenium deficiency from the increasing use of home grown feeds as a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…No statistically significant relation was found between the blood glutathione peroxidase activities of Anderson et al (1979) and the selenium concentration of grain and conserved herbage from the same farms given here, but both studies point to the need to consider selenium supplements for grazing animals and those given only feeds grown on the farm.…”
Section: Se Concentration Of Grain and Herbagecontrasting
confidence: 60%
See 1 more Smart Citation
“…No statistically significant relation was found between the blood glutathione peroxidase activities of Anderson et al (1979) and the selenium concentration of grain and conserved herbage from the same farms given here, but both studies point to the need to consider selenium supplements for grazing animals and those given only feeds grown on the farm.…”
Section: Se Concentration Of Grain and Herbagecontrasting
confidence: 60%
“…Also a survey of glutathione peroxidase values of the blood of sheep on farms in England, Scotland and Wales showed that a high proportion had a low selenium status, as indicated by low enzyme activity (Anderson, Berrett & Patterson, 1979). The selenium concentration of feeds grown on a number of the same farms in England and Wales as those from which Anderson et al (1979) obtain blood samples, was determined. These are reported here, together with values for a range of specific herbage species.…”
Section: Introductionmentioning
confidence: 99%
“…0.019) mmol/l. Reference values for blood Se concentrations include: ,1.52 mmol/l (Stowe and Herdt, 1992), ,1.00 mmol/l (Puls, 1994), ,0.95 mmol/l (Anderson et al, 1979), and for lamb blood Se concentrations ,0.13 mmol/l Grace and Knowles, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Selenium deficiencies have been reported in soils, herbages and consequently in livestock blood concentrations in USA (Van Metre and Callan, 2001), Australia (Tinggi, 2003), New Zealand (Watkinson, 1983) and also within the UK (Blaxter, 1963;Anderson et al, 1979;Wang et al, 1987) and Ireland (Mee et al, 1994). In Northern Ireland in particular, McMurray and Rice (1982) have reported the Se status of livestock to be highly deficient with 85% of beef herds being below the threshold of what is considered adequate.…”
Section: Introductionmentioning
confidence: 99%
“…37,000 samples over 30,000, or 95 per cent, are from the north-east; Sinclair, 1987: personal communication) and in Veterinary Investigation Service surveys for endemic elemental deficiencies (e.g. Anderson et al, 1979). National farm revenues are declining, and English cereal farmers show an increasing interest in rearing sheep, the principal land product in the west (Buxton, 1986).…”
Section: The Islands and Highlands In Lawmentioning
confidence: 97%